2019
DOI: 10.1002/cphc.201900166
|View full text |Cite
|
Sign up to set email alerts
|

An International Laboratory Comparison Study of Volumetric and Gravimetric Hydrogen Adsorption Measurements

Abstract: In order to determine a material's hydrogen storage potential, capacity measurements must be robust, reproducible, and accurate. Commonly, research reports focus on the gravimetric capacity, and often times the volumetric capacity is not reported. Determining volumetric capacities is not as straight‐forward, especially for amorphous materials. This is the first study to compare measurement reproducibility across laboratories for excess and total volumetric hydrogen sorption capacities based on the packing volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…Previous interlaboratory exercises, performed on both nanoporous carbons [116] and MgH 2 , [117] have demonstrated the difficulties that can be encountered when trying to achieve reproducibility between results obtained in different laboratories. [36] Recent efforts by Hurst and co‐workers, on nanoporous carbons, have achieved more consistent results,[ 118 , 119 ] but the disparity observed in the earlier exercises[ 116 , 117 ] does not inspire confidence in the likely veracity of all independently determined results published in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous interlaboratory exercises, performed on both nanoporous carbons [116] and MgH 2 , [117] have demonstrated the difficulties that can be encountered when trying to achieve reproducibility between results obtained in different laboratories. [36] Recent efforts by Hurst and co‐workers, on nanoporous carbons, have achieved more consistent results,[ 118 , 119 ] but the disparity observed in the earlier exercises[ 116 , 117 ] does not inspire confidence in the likely veracity of all independently determined results published in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Round robin testing and investigation of literature metadata have provided even more evidence for large variabilities of adsorption measurement data. , Two recent studies conducted by Sholl and co-workers particularly provide useful insights into the scale of the reproducibility problem in this area. , In one example, Park et al examined thousands of experimental adsorption isotherms reported in the NIST/ARPA-E Adsorption Database and collected all CO 2 adsorption isotherms for MOFs. First of all, they found that even for the widely studied case of CO 2 adsorption, there are only 15 MOFs with adequate replicates in the literature that can be used in a reproducibility test.…”
Section: Challenges Of Multiscale Materials Screening: Accuracy Data ...mentioning
confidence: 99%
“…Fig. S12-S13 displays the NREL excess and calculated total (Ntot) (Supporting Information, Equation 6) H2 uptakes at 75.6 and 303 K for comparison (38)(39)(40). Figure 5b shows the absolute (Nabs) volumetric adsorption isotherms of H2 at 75.6 K in monoHKUST-1 compared with a densified HKUST-1 powder and a simulated H2 isotherm for HKUST-1.…”
Section: Hydrogen Storage Performancementioning
confidence: 99%